PERENCANAAN PENGELOLAAN DAS TERPADU DALAM MENGATASI KETIDAKSEIMBANGAN KEBUTUHAN AIR BERSIH DAN PERMASALAHAN BANJIR (KAJIAN DAERAH ALIRAN SUNGAI CISADANE) - Endah Lestari; Ranti Hidayawanti (FORUM MEKANIKA, 2016)
The imbalance between supply and demand of water needed to do assessment of water availability and needs good water for balance. Development of the region in certain areas led to increased water demand due to population growth. Watershed Development seeks to manage the relationship hydrology to optimize use of natural resources for conservation, productivity, and poverty reduction. To achieve this requires a coordinated management of the various resources in the watershed, including forests, farms, agricultural land, surface and underground water through the hydrologic processes (Kerr, 2007). Cisadane River is the largest contributor to the water source for the residents of Tangerang City and surrounding areas. With the increasing development of all aspects of life, as the impact of population growth and development in an area, it also increases the needs and demands of water services that require water allocation management. Planning for Watershed Management Cisadane divided into three parts, the first watershed upstream side based on the functions of conservation managed to maintain the environmental conditions of the watershed that is not degraded, which among other things can be indicated on the condition of vegetation cover land watersheds, water quality, the ability to store water (discharge), and rainfall. Both DAS middle part is based on the function of the utilization of river water that managed to provide benefits to the social and economic interests, which among other things can be indicated from water quantity, water quality, the ability to deliver water, and the height of the ground water level, as well as related to the maintenance of water infrastructure such as management of rivers, reservoirs and lakes. The third watershed downstream part is based on the function of the utilization of river water that managed to provide benefits to the social and economic interests, as indicated by the quantity and quality of water, the ability to deliver water, height of rainfall, and related to the needs of agriculture, clean water, and water management wast